Теоретичні аспекти підвищення конкурентоспроможності людських ресурсів в контексті цифрової трансформації економіки - Кіріченко, О. В.; Kirichenko, O. (ЦНТУ, 2020)
Стаття присвячена порівняльному аналізу сутності поняття «конкурентоспроможність» по відношенню до людських ресурсів та інших подібних категорій, ідентифікації їх переваг, недоліків та сфери застосування в умовах цифровізації економіки і життя суспільства. Наведено характеристику рівнів формування конкурентоспроможності людських ресурсів (особистісного, мікроекономічного, галузевого, територіального, макроекономічного та глобального). Запропоновано напрями підвищення конкурентоспроможності людських ресурсів в умовах сучасних реалій. The paper is devoted to the comparative analysis of the essence of the concept of "competitiveness" in relation to human resources and other similar categories, identification of their advantages, disadvantages and scope in terms of digitalization of the economy and society. It was determined that in the context of digitalization it is expedient to apply the approach to studying the process of forming the competitive advantages of human resources, as allows to consider the competitive advantages in relation to all age groups and at all stages of forming and development of competitiveness. Today, such qualitative advantages as the ability of intensive using of the modern information and communication technologies, digital literacy, interpersonal skills, ability to work in a team, focus on achieving the end result are becoming very important. The characteristics of the levels of forming of the competitiveness of human resources (personal, microeconomic, sectoral, territorial, macroeconomic and global) were given. The urgency of forming and development of global competitiveness of human resources in the conditions of modern realities was emphasized.
Theoretical Aspects of Improving the Competitiveness of Human Resources in the Context of Digital Transformation of the Economy
Теоретические аспекты повышения конкурентоспособности человеческих ресурсов в контексте цифровой трансформации экономики
Keywords: людські ресурси; конкурентоспроможність; конкурентна перевага; цифрова економіка; цифровізація; human resources; competitiveness; competitive advantage; digital economy; digitalization; человеческие ресурсы; конкурентоспособность; конкурентное преимущество; цифровая экономика; цифровизация